Theoretical and Conceptual Basis of Budget Security: Regional and Local Dimension - Halyna Voznyak; Taras Kloba (Vasyl Stefanyk Precarpathian National University, 2021)
In current conditions, budget security is one of the essential components of financial security. The budget is the leading financial plan of the state and reflects most of the economic processes in the country; it also redistributes and accumulates revenues, provides financing of vital costs. Proper use of the budget as a financial basis for state regulation of a market economy should ensure the rule of economic and social processes in the interests of society to create conditions for the economic development of the country. Оn the one hand, and Budget security reflects the regularities of the functioning of the budget as an objective reality and, on the other hand, the subjective manifestations of human activity that find their expression in fiscal policy.The article aims to substantiate budget security's theoretical and conceptual basis at the regional and local levels.The article examines the theoretical essence of budget security at the regional and local levels. First, scientific approaches to the definition of "budget security" are generalized. Second, budget risks are considered, which under the influence of certain factors can be transformed into threats to budget security (discrete control; insolvency of taxpayers; political, military actions; destabilization of the financial sector of the region/communities; imbalance of revenues and expenditures; structure of revenues and expenses; external dependence violation of the stability of payments, debt growth (internal/external), stochastic errors, corrupt growth of the shadow sector, irrational budgeting). Third, the theoretical conceptualization of the concept of "threat", their essence and characteristics are substantiated. Fourth, understanding the nature of the concept of "budget risk" and "threat to budget security" is investigated. Finally, the functions and tasks that the budget security of territories should perform in the conditions of increasing financial and economic instability are considered.Coverage of the theoretical and conceptual basis of budget security of regions and communities, specification of existing and potential factors and risks of budget security, functions and tasks of budget security will minimize and neutralize various aspects and threats in budget security and increase budget security at regional and local levels and achieve important strategic guidelines.